THE IMPORTANCE OF THE “GREEN CAMPUS” MODEL IN ENHANCING THE SUSTAINABILITY OF HIGHER EDUCATION INSTITUTIONS - Dilshod Qurbanov (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article analyzes the importance of the “Green Campus” model in ensuring sustainable  development  in  higher  education  institutions.  During  the  research,  the advantages of this model were examined based on environmental, economic, and social aspects. Furthermore, foreign and local experiences were studied, existing problems were identified, and proposals for their elimination were developed. The results show that  the  green  campus  model  is  an  important  tool  for  effectively  organizing  the activities of higher education institutions and developing environmental culture.